PENGARUH KOMPETENSI APARAT DESA, KOMITMEN ORGANISASI DAN PARTISIPASI MASYARAKAT TERHADAP KEBERHASILAN PENGELOLAAN KEUANGAN DESA (Sudi Kasus Desa Buntongi Kec.Ampana Kota Kab.Tojo Una Una) - Siti Aminah H. Karim; Mahmud Lahay; Zulfan Monoarfa; Rosida P. Adam; Suardi S (Syarif Hidayatullah State Islamic University Jakarta, 2019)
In the administration of governance and development, a source of village financial income is needed, for this the organizational commitment of the village government towards the authority, duties and responsibilities of implementing village financial management is transparent and accountable. The purpose of this study was to determine and analyze the extent of the influence of the competence of village officials, organizational commitment and community participation on success in village financial management. This type of research is a mixed method by combining qualitative and quantitative research with sampling techniques by saturated sampling. The number of respondents was 40 people. Analysis tools with SWOT analysis and multiple linear regression. The results showed that the simultaneous probability of village officials, organizational commitment and community participation have a direction of significant influence on the success of village financial management.